Disembodied Surreal Tendencies of Silent Hill the Film: Traces of Japanese Abreaction Terror - Jaka Pratama, Andreas (Bina Nusantara University, 2023)
The Silent Hill live action cinema was an adaptation of a survival horror videogame title that explored the theme of loss, delusion, but also of internal conflict that leads to the ultimate self-redemption. Through the psychoanalytical reading, the surreal tendencies and symbolisms are analysed, the signs of abreaction terror sourced historically from the post-war Japan made manifest. This article looks at the possible point of origin of the surreal symbolism utilized by first the videogame iterations, then secondly the adaptation to the silver screen which may not translate into its contextually accurate adaptation. Exposing the roots of such subconscious historical trauma realizes how much the live action films made disembodiment of that spirit resulting in its failure to reach down deeper into the source material.